Strategies, Oversight, and Enforcement of Ukrainian Employment Law Compliance - Kucher, Oleksii; Mohilevskyi, Leonid (Journal of Ecohumanism, 2024)
Developing and implementing an effective supervision system and adherence to labour legislation is currently regarded as an essential component of the managerial paradigm. During the research process, the targeted functionality of the supervision and control system was identified, encompassing regulatory, law enforcement, regulatory, informational, managerial, and educational functions. This study aimed to assess the effectiveness of state policy on supervision and control over compliance with labour legislation, analyse the volumes and number of violations in the field of labour legislation, and establish the correlations between the effectiveness of state policy and the number of existing violations in the field of labour legislation. The research methods employed in-cluded logical-semantic, systemic-functional, and structural-logical methods, the method of expert survey, the integral method, and Pearson correlation analysis. Results of the research indicated that the effectiveness of state policy, supervision, and control over compliance with labour legislation in Ukraine was rated at a level of Ef policy Group 1 = 5.99 by scientific experts and Ef policy = 7.36 by officials. Notably, officials gave a higher rating to the policy compared to experts.